Feed-based vaccination regime against streptococcosis in red tilapia, Oreochromis niloticus x Oreochromis mossambicus - Md Salihin, Muhammad Ismail; Abdullah, Siti Zahrah; Mohammad Ridzuan, Mohd Syafiq; Azmai, Mohammad Noor Amal; Nawi, Mohd Firdaus; Saad, Mohd Zamri (BioMed Central, 2016)
Background: Streptococcosis is an important disease of tilapia throughout the world. In Malaysia, streptococcosis outbreak was commonly reported during the 3-month period of high water temperature between April and July. This study describes the duration of protection following single and double booster dose regimes against streptococcosis in tilapia using a feed-based vaccine containing formalin-killed Streptococcus agalactiae. A total of 510 tilapias of 120 ± 10 g were selected and divided into 3 groups. Fish of Group 1 were vaccinated at weeks 0 and 2 (single booster group) while fish of Group 2 were vaccinated at weeks 0, 2 and 6 (double booster group) with a feed-based vaccine against streptococcosis. Fish of Group 3 was not vaccinated. Serum samples were collected weekly to determine the antibody level while samples of eye, brain and kidney were collected for bacterial isolation. At week 10, all fish were challenged with live S. agalactiae and the survival rate was determined. Results: Both vaccinated groups showed significant (p < 0.05) increase in the antibody levels following the first booster dose, which lasted until week 6. Group 2 showed consistent high level of antibody following the second booster dose at week 6 and remained high until week 12. Challenge trial at week 10 resulted in 45 %, 70 % and 0 % rate of survival for Groups 1, 2 and 3, respectively. Conclusion: Double booster regime is most suitable to be applied for feed-based vaccination against streptococcosis prior to the start of the hot season.